Performance analysis of PV/T Combi with water and air heating system: An experimental study. (February 2016) - Othman, M.Y.; Hamid, S.A.; Tabook, M.A.S.; Sopian, K.; Roslan, M.H.; Ibarahim, Z.
Abstract: A hybrid photovoltaic thermal (PV/T) solar collector is well-known on its capability to generate electrical and thermal energy, simultaneously. Producing more thermal energy during the process contribute to poor performance on the electrical efficiency of the solar cells. Water and air can help by acting as the heat removal medium. Alternatively, this waste energy can be manipulated to produce hot air/water system. The paper presents the integration of both medium with the conventional PV/T collector. Major components fabricated in the system are two transparent photovoltaic modules connected in parallel as to generate electricity, double pass flat plat air collector, copper water tube and a storage tank as to store hot water produced. Experimental values on solar cell temperature, water temperature and air temperature on both channels have been measured. The performance of the system is calculated based on Hottel–Whillier–Bliss equation. Under controlled indoor environment at radiation level of 800 W/m 2, air flow rate at 0.05 kg/s and water flow rate at 0.02 kg/s; the outlet temperature indicated reading of 27.4 °C. This is the best results from the overall experiment. The electrical efficiency achieved was 17% with average electrical power of 145 W and thermal efficiency accomplished was 76%. Highlights: A PV/T Combi system based on air and fluid-based is proposed. The performance of the bi-fluid PV/T system is evaluated. The proportionality of mass flow rate and thermal efficiencies can be observed. The system performance is investigated by experimental procedure.